Human Resource Planning for the 21st Century - Fahed-Sreih, Josiane (IntechOpen, 2018)
Since the dawn of civilization, humans were selected, allocated and organized based on their skills and job criteria. Today, the role of Human Resources (HR) professionals goes beyond recruitment and management of human capital. Human Resource Planning for the 21st Century tackles the current trends of human resource management (HRM) and human resource planning while highlighting certain roles that HR professionals are involved in. Human Resource Planning for the 21st Century explores HRM systems and their roles within a corporate setting, elaborates on HR plans for crises, uncovers the effects of downsizing on company brand and looks at the possible impact of globalization on corporate social responsibility and HRM.